2017
DOI: 10.1111/jopr.12710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distal Implant Inclination on Dislodging Forces of Different Locator Attachments Used for Mandibular Overdentures: An In Vitro Study

Abstract: Axial and nonaxial retention of Locator attachments for implant-retained overdentures are significantly affected by the degree of distal implant inclination and the type of nylon inserts. Lm is recommended to retain overdentures when implants have 5° or 10° distal inclination, and Le and Ll are recommended with 20° inclination to maintain high axial and nonaxial retention after wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…Sample size calculation was based on the results of Stephens et al, Mínguez-Tomás et al, and Elsyad et al [17,27,28], with a power of 0.8 and a level of significance of 0.05. In total, 96 individual attachment combinations were produced for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculation was based on the results of Stephens et al, Mínguez-Tomás et al, and Elsyad et al [17,27,28], with a power of 0.8 and a level of significance of 0.05. In total, 96 individual attachment combinations were produced for this study.…”
Section: Methodsmentioning
confidence: 99%
“…When an implant is placed, especially in the anterior mandible, the implant tends to be buccally or lingually inclined because of the anatomy of the ridge in this area. However, use of an appropriate insert prevented the decrease in retention in patients with angulated implants [9,10]. Locator attachments are now frequently used with 1-IODs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Rutkunas et al concluded that only minimal changes in the inner diameter of the metal housing of the plastic inserts are induced by simulated wear . Observational data based on analysis, stereomicroscopic photographs, and digital micrometric measurements confirmed the presence of dimensional changes, deformation, and surface alterations of the interchangeable plastic inserts following cyclic seating‐unseating . Surface wear tends to be more expressed on the central stud than on the outer ring of the plastic insert in contact with the metal undercuts of the Locator abutment …”
mentioning
confidence: 99%
“…3 The most common prosthetic complication associated with the use of the Locator system is loosening of the retentive mechanism. 4,5 Chemical and thermal factors such as exposure to lubricants and biologic fluid environments, 6 denture cleansers, [7][8][9] or high temperatures, 10 as well as mechanical factors such as repeated insertion-removal cycles of the prosthesis, [11][12][13][14][15] implant angulation and interimplant divergence, [16][17][18][19][20][21][22][23][24][25] abutment height, 26 mastication, 27,28 and type of dislodging forces 29 have been demonstrated to negatively affect the retention of Locator attachments. 25,26 The exact mechanisms by which mechanical factors result in retention loss of the Locator system are poorly documented.…”
mentioning
confidence: 99%
See 1 more Smart Citation